Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus Terhadap Belanja Modal(Studi Empiris Pada Kabupaten/Kota Wilayah Jawa Tengah Tahun 2014) - Rudiansah, Nova, Fauzan S.E., M.Si., Ak (2017)
This study aimed to examine the effect of economic growth, revenue (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) towards capital expenditure budget allocation in the counties and cities in the region of Central Java province in the period 2014. In this study, the sampling method used was saturated sampling technique in which the entire population will be used as a sample. The data used in this research is secondary data obtained from the Director General of Fiscal Balance website via the Internet and Local Government Central Statistics Agency (BPS). Data obtained from the Director General of Fiscal sites Local Government Finance in the form of budget realization reports concerning revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK) and Capital Expenditure in 2014. Meanwhile, the Central Statistics Agency (BPS) Data obtained Gross Regional Domestic Product according to constant prices of 2014. the methods used to analyze the data is multiple linear regression analysis method. The results of this study indicate that the economic growth had no effect on capital spending. This is demonstrated by the significant value (sig t) variable economic growth by 0.402 (> = 0.05). PAD effect on capital spending. This is demonstrated by the significant value (sig t) variable PAD 0,000 (< = 0.05). DAU has no effect on capital spending. This is demonstrated by the significant value (sig t) variable DAU amounting to 0.928 (> = 0.05). DAK has no effect on capital spending. This is demonstrated by the significant value (sig t) variable fund at 0.129 (> = 0.05).